Pengembangan Platform E-Commerce Toko Amesha Lightworks Berbasis UI/UX Design untuk Optimalisasi Customer Journey - Sauca Ananda Pranidana; Firmansyah Firmansyah; Mella Marcelena; Syahqim Sudarpo; Aishafa Cahya Amaradani; Astrid Fadila Sari (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The rapid development of e-commerce in Indonesia requires the provision of digital platforms that are not only functional but also prioritize user experience. This study aims to develop the AMESHA Lightworks e-commerce platform with a customer journey-based UI/UX approach to optimize sales conversion. It uses the Double Diamond method, which consists of discover, define, develop, and deliver. The initial phase involved analyzing user needs through a customer journey mapping study, followed by the creation of a high-fidelity prototype using Figma, which was then tested for usability. The prototype was then developed into a functional platform using modern web technology. Based on the evaluation of the prototype, an e-commerce platform with intuitive navigation and a responsive interface was produced, emphasizing the simplification of the checkout process from 5 to 3 steps and the optimization of the visualization of lighting furniture products. Usability testing showed an increase in task success rate by a certain percentage and a decrease in checkout completion time by a certain percentage at the end of the trial. The implementation of a customer journey-based UI/UX approach was quite effective in improving customer experience and sales conversion on the Toko AMESHA Lightworks e-commerce platform, and provided practical contributions to the development of furniture and lighting MSMEs in the digital era.